(untitled) (Journal of Economic Research & Business Administration, 2015)
Heterogeneity of economic space, irregularity of regional development are characteristic for any state as a social-economic system. Aim of the regional policy is consideration of interregional differences to determine potential and directions of the social-economic development. There are various approaches to the typology of negative regions and their crisis groups. Characteristics in the level of employment and formation of labor market in regions propose opportunity of the regions’ grouping by interrelated social-economic factors. The article considers analysis indicators of the labor market. It defines criteria to detect regions with critical situation at the regional labor market. It gives calculations on administrative-territorial entities of SKO in a crisis period. It has defined interval scales of the administrative-territorial entities’ distribution by condition of the labor market depending on the critical situation at the market with a view to detect depressive regions.